The Influence of Content Marketing Instagram on Consumer Purchase Decisions (Study at Almeera Atelier) - Al Aziz, Ilham Medi; Fauziyah, Azizah; Koeswandi, Tika Annisa Lestari (A Social Science and Entrepreneurship Journal, 2022)
The purpose of this research is to find out: (1) To find out how the general description related to content marketing and consumer purchasing decisions at the Almeera Atelier company (2) To determine the effect of content marketing on Almeera Atelier consumer purchasing decisions. This study uses 2 variables to test the effect, namely the independent variable, in this study is content marketing (X) and the dependent variable is purchasing decisions (Y). This study uses quantitative data analysis techniques involving 100 samples, namely followers of Almeera Atelier. The result of this research is that there is a positive and significant influence between content marketing and purchasing decisions. This is known by conducting a t-test and one-tailed test which states that there is a positive correlation or significant influence between content marketing (X) on purchasing decisions (Y) at Almeera Atelier. This means that the ability of the independent variable to explain the dependent variable is 44%, the rest is explained by other variables not discussed in this study, such as the influence of influencers, the use of paid advertising and others.